The influence of the ‛environmentally-friendly’ character through asymmetries on market crash price of risk in major stock sectors - Dimitriadis, Konstantinos A.; Koursaros, Demetris; Savva, Christos S. (My University, 2024)
This paper investigates the impact that the ‛green character’ of stocks generates on their market price of risk. The study covers a spectrum of international large-cap stocks in influential sectors since 1 January 2013 up to 5 July 2022. Focusing on the asymmetric and shape features of price risk, econometric outcomes reveal that well-established (Industrials) or highly profitable (Technology) sectors are less affected by the skewness/kurtosis price of risk or the ‛environmentally-friendly’ features. On the contrary, sectors vulnerable to alterations in income or wealth, such as Financials and Real Estate are more sizably influenced by negative asymmetry, kurtosis, and the higher volatility in bear markets. The ‛green character’ lowers the market price of stocks, increases risk premia due to higher probability for downwards movements and renders investors more risk-averse and nevertheless, this impact only reflects the initial period of green innovation with high anti-polluting costs as the green label could prove to be greatly beneficial in the future.
Keywords: Skewness; Green investing; Asset pricing; Price of risk; Kurtosis